Isolation and characterization of resistant gene analogs in cassava, wild Manihot species, and castor bean (Ricinus communis) - Gedil, Melaku A; Kumar, M.; Igwe, D. (Academic Journals, 2012)
Cassava, Manihot esculenta, is one of the major food crops in sub-Saharan Africa (SSA) providing the bulk of dietary calories to hundreds of millions of households. Two viral diseases, namely cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) pose a serious threat to cassava production. The emergence of new virus species and strains that overcome the existing resistant/tolerant cultivars entails identification and pyramiding of new sources of resistance using marker-aided selection. The isolation of resistance gene analogues (RGAs) using a homology-based approach can provide useful resources towards this goal. Degenerate primers based on the conserved motif of the nucleotide binding site (NBS) domain from resistance (R) genes were used to isolate RGAs from genomic DNA and cDNA in cassava, wild Manihot species, and castor bean (Ricinus communis). A total of 552 RGAs sequences were identified and deposited in GenBank. Conserved motifs such as P-loop, Kinase-2a and GLPL were present in the NBS domain. This study sheds light on the nature of NBS- leucine-rich repeat (LRR) R genes in cassava and closely related taxa in the family Euphorbiaceae. These candidate sequences mapped to the draft cassava genome with high sequence similarity to predicted NBS-LRR genes. These novel sequences may serve as a stepping stone for further characterization and experimental validation of predicted R genes in the draft cassava genome, ultimately leading to the development of functional gene-targeted markers that can be used in molecular resistance breeding aimed at combating CBSD and CMD.